Pengaruh Model Project Based Learning Berbantuan Media Mind Mapping terhadap Keterampilan Menulis Teks Berita Siswa Kelas VII MTsN 1 Kota Padang - Wardana, Maylanie Putri; Ridha Hasnul Ulya; Farel Olva Zuve; Mita Domi Fella Henanggil (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe three aspects, namely the level of news text writing skills of seventh-grade students at MTsN 1 Padang City before and after the implementation of the Project Based Learning model assisted by mind mapping media, as well as the effect of the application of this model on students’ news text writing skills. The type of research used is quantitative research with an experimental method, employing a one-group pretest–posttest design. The population of this study consisted of all seventh-grade students of MTsN 1 Padang City, totaling 345 students. The research sample was determined using purposive sampling technique, namely students of class VII 6 consisting of 25 students. Data collection techniques were carried out through performance tests in the form of pretests and posttests of news text writing skills. The data analysis techniques used included normality test, homogeneity test, and hypothesis testing. The results showed that the average score of students’ news text writing skills before the implementation of the Project Based Learning model assisted by mind mapping media was 49.83, classified as Nearly Sufficient (NS), while the average score after the implementation increased to 74.83, classified as More than Sufficient (MtS). The results of the t-test indicated that the alternative hypothesis (H1) was accepted at a 95% significance level with degrees of freedom n–1, because the calculated t-value (14.59) was greater than the t-table value (1.71). In addition, the N-Gain Score calculation result of 0.50 falls into the moderate category; however, the effectiveness level of 50% is classified as less effective. Nevertheless, the application of the Project Based Learning model assisted by mind mapping media is still considered feasible because it is able to improve students’ news text writing skills, although adjustments are still needed to achieve a more optimal level of effectiveness.